Takayasu Arteritis: A current perspective on diagnosis and emerging treatments - Nitschke, Nicole; Mocarska, Martyna; Orłowska, Anna; Strakowska, Katarzyna; Opalska, Laura; Maryńczak, Anna; Muciek, Adrianna; Mencel, Jan; Lenar, Marta; Lenar, Filip (Quality in Sport, 2025)
Takayasu-Arteritis (TA), also known as the pulseless disease or aortic arch syndrome is a rare but serious condition that primarily affects mainly the large blood vessels. This inflammatory vascular disease is characterised by intimal fibrosis and vessel narrowing, especially affecting the aorta, its branches and the pulmonary arteries. Patients typically present asymptomatic but such conditions as weak or absent pulses in arms or legs, angina pectoris and stroke-like symptoms can appear in severe cases. A comprehensive understanding of TA disease is essential for prompt diagnosis and effective management. This review will examine the historical context, symptoms, diagnostic criteria, new therapeutic approaches, and future directions in research and treatment.